Answer:
B
Step-by-step explanation:
When graphed the circle has a point in (-4,-3) and the center is (-8,-6)
I hope this is right i think the answer is 40
−2x + 3y + 5z = −21
−4z = 20
6x − 3y = 0
do -4z=20 first
divide both sides by -4 to get z by itself
-4z/-4=20/-4
z=-5
Use z=-5 into −2x + 3y + 5z = −21
-2x+3y+5(-5)=-21
-2x+3y-25=-21
move -25 to the other side
sign changes from -25 to +25
-2x+3y-25+25=-21+25
-2x+3y=4
6x-3y=0
find x by eliminating y
Add the equations together
-2x+6x+3y+(-3y)=4+0
-2x+6x+3y-3y=4
4x=4
Divide by 4 for both sides
4x/4=4/4
x=1
Use x=1 into 6x − 3y = 0
6(1)-3y=0
6-3y=0
Move 6 to the other side
6-6-3y=0-6
-3y=-6
Divide both sides by -3
-3y/-3=-6/-3
y=2
Answer:
(1, 2, -5)
Your answer would be (x,y)=(2,-2)
Answer:
<em>C. y = 3x + 13.</em>
Step-by-step explanation:
The point slope form of a line is
y - y1 = m(x - x1) where m = the slope, and (x1, y1) is a point on the line.
So, substituting:
y - 1 = 3(x - -4)
y - 1 = 3(x + 4)
y = 3x + 12 + 1
y = 3x + 13.